2018
DOI: 10.1038/s41598-018-31674-1
|View full text |Cite
|
Sign up to set email alerts
|

Genetic screen in myeloid cells identifies TNF-α autocrine secretion as a factor increasing MDSC suppressive activity via Nos2 up-regulation

Abstract: The suppressive microenvironment of tumors remains one of the limiting factors for immunotherapies. In tumors, the function of effector T cells can be inhibited by cancer cells as well as myeloid cells including tumor associated macrophages and myeloid-derived suppressor cells (MDSC). A better understanding of how myeloid cells inhibit T cell function will guide the design of therapeutic strategies to increase anti-tumor responses. We have previously reported the in vitro differentiation of MDSC from immortali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 38 publications
0
19
0
Order By: Relevance
“…Studies have suggested that inflammatory factors could contribute to the expansion and recruitment of MDSCs, such as C-X-C motif chemokine ligand 2 (CXCL2), hepatocyte growth factor (HGF) or tumor necrosis factor alpha (TNF-α). [42][43][44] Nevertheless, a direct association between MDSC and these mediators has not been identified.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have suggested that inflammatory factors could contribute to the expansion and recruitment of MDSCs, such as C-X-C motif chemokine ligand 2 (CXCL2), hepatocyte growth factor (HGF) or tumor necrosis factor alpha (TNF-α). [42][43][44] Nevertheless, a direct association between MDSC and these mediators has not been identified.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in ovarian cancer cell lines, TNFα can behave as a signaling molecule within the producing cell or among the surrounding ones, and can induce CXCR4 expression through NF-κB, enhancing in this way cell invasion (170,171). Moreover, it has been proved that TNFα secretion by MDSCs in the tumor bed acted as an autocrine cytokine that enhances their T lymphocyte suppressive activity by upregulating different genes associated with immunosuppression, like Nos2 (172).…”
Section: Tnfα and The Immune Response Against Cancermentioning
confidence: 99%
“…Several CRISPR-mediated investigations have performed to determine key regulatory elements contributing to cancer immunotherapy and the results have revealed the role of granulocyte–macrophage colony-stimulating factor in CD19 CAR T-cells administration [ 141 ], TNF-α autocrine level in performance of myeloid-derived suppressor cells [ 142 ], lysosome-associated membrane protein type 2a in regulation of tumor-associated macrophages [ 143 ], histone demethylase LSD1 in stimulation of anti-tumor responses [ 144 ], transcriptional co-activator with PDZ-binding motif in PD-L1 level [ 145 ], and Foxp3 + Treg cells in tumor advancement [ 146 ], to name a few.…”
Section: The Deluxe Zone Of Cancer Therapy Where Crispr Meets Immunomentioning
confidence: 99%